2006
DOI: 10.1051/0004-6361:20054795
|View full text |Cite
|
Sign up to set email alerts
|

SiO in C-rich circumstellar envelopes of AGB stars: effects of non-LTE chemistry and grain adsorption

Abstract: Aims. New SiO multi-transition millimetre line observations of a sample of carbon stars, including J = 8 → 7 observations with the APEX telescope, are used to probe the role of non-equilibrium chemistry and the influence of grains in circumstellar envelopes of carbon stars. Methods. A detailed radiative transfer modelling, including the effect of dust emission in the excitation analysis, of the observed SiO line emission is performed. A combination of low-and high-energy lines are important in constraining the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
99
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 26 publications
14
99
2
Order By: Relevance
“…(2) and that the size of the SiO emitting region does not differ significantly between the different chemical types. This is in agreement with the results of Schöier et al (2006b). Figure 6a shows our mass-loss-rate results for the S-type AGB star sample compared with previous results for carbon stars Table 6.…”
Section: Sio Abundances and Radial Distributionsupporting
confidence: 91%
See 3 more Smart Citations
“…(2) and that the size of the SiO emitting region does not differ significantly between the different chemical types. This is in agreement with the results of Schöier et al (2006b). Figure 6a shows our mass-loss-rate results for the S-type AGB star sample compared with previous results for carbon stars Table 6.…”
Section: Sio Abundances and Radial Distributionsupporting
confidence: 91%
“…There exists strong evidence that the circumstellar SiO emission carries information on the region where the mass loss is initiated and where the dust formation takes place (Reid & Moran 1981;Reid & Menten 1997;Schöier et al 2006a) making it a particularly interesting molecule to study. Schöier et al (2006b) modelled circumstellar SiO line observations from a sample of carbon stars and when comparing this to a similar analysis performed by González Delgado et al (2003) for a large sample of M-type AGB stars, they found no apparent distinction between their circumstellar SiO abundance distributions. For the carbon stars, the derived abundances are several orders of magnitude higher than expected from thermal equilibrium stellar atmosphere chemistry.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…More generally, Cherchneff (2006) studied the inner wind composition as a function of the carbon-to-oxygen (C/O) ratio of the stellar photosphere and confirmed the formation of O-bearing species in carbon stars and that of C-bearing molecules in O-rich AGB stars as a result of non-equilibrium chemistry induced by periodic shocks. Several observations of high energy rotational transitions of HCN, SiS, CS, and SiO in AGBs and supergiants at mm and submm wavelengths corroborated these results (e.g., Schöier et al 2006Schöier et al , 2007Ziurys et al 2007Ziurys et al , 2009Decin et al 2008).…”
Section: Introductionmentioning
confidence: 56%